Thermochemical Preparation and Properties of Low-Cost Polylanthanide Manganite Materials of Ln(La, Ce, Nd, Pr)xCayMnO3-Type with Perovskite-Fluorite Structure - V. A. Gorbunova; L. M. Sliapniova; A. V. Gorbunov (Наука и техника)
A physical and chemical investigation of ceramic materials based on manganites of mixed rare earth elements  –  La0,8-хLnхCa0,2Mn0,94Cr0,04Ni0,02O3  –  for electrochemical and catalytic applications has been carried out, and   they were obtained from nitrate feedstock based on industrial-type polylanthanide concentrate, which corresponds to typical bastnaesite ore on the ratio of rare-earth elements in it. For polycrystalline samples of the obtained materials, the formation of single-phase structure or more often two-phase one has been identified after sintering in air at 1500 K, i. e., a the mixture of cubic perovskite phase based on low-cerium or A-site deficient manganite and a fluorite phase based on CeO2 with dioxide content of 54–98 %. A phase formation mechanism has been proposed, which is possible during the transition to compositions with rising cerium content at a constant sintering temperature of  manganite materials. The effect of the chemical composition and structure of the materials on their conductivity and density, reached by the sintering, has been established in the paper. Investigation of electrical conductivity has shown that in the manganites the semi-conductive behavior/ charge transfer mechanism (p-type) is realized at the temperature range of (300–1270) K. The maximum conductivity within the range of (290–1270) K is achieved in this low-cerium bastnaesite-type system for a two-phase material with the composition La0,8-хLnхCa0,2Mn0,94Cr0,04Ni0,02O3 at x= 0.6 and is 39 S/cm at a density level of 50 % of the theoretical one for a ceramic sample. Manganite materials with lanthanum substitution, such as investigated polylanthanide-based ones, can provide a lower cost for fabrication of electrochemical and other devices based on them, taking into account the complex prices dynamics on the markets of rare-earth raw materials during the last decade.